PENGARUH PERILAKU KONSUMEN DI MASA PANDEMI COVID-19 TERHADAP KEPUTUSAN PEMBELIAN KEBUTUHAN POKOK MASYARAKAT KOTA BANDA ACEH - Teuku Haswan Chalid; Deni Yanuar; Novi Susilawati (Jurnal Ilmiah Mahasiswa Fakultas Ilmu Sosial & Ilmu Politik, 2023)
The presence of the Covid-19 pandemic that has swept the world has not only had an impact on the economy, but has also had an impact on changes in consumer behavior in fulfilling basic needs thereby influencing consumer behavior. In addition, the Covid-19 pandemic has affected consumer decisions in purchasing primary, secondary and everyday products. This research is located in the city of Banda Aceh using a quantitative approach. This study uses a survey method in which the researcher asks several people about past or present beliefs, opinions, characteristics of an object and behavior. To determine the sample for the study, the researcher used the Slovin formula using a purposive sampling technique to get the result that consumer behavior (X) during the Covid-19 pandemic had an effect, this was evidenced by the acquisition of a significance value from the t test of 0.00 0.05. The results of the coefficient of determination obtained stated that consumer behavior (X) could explain the variance of the purchase decision variable (Y) during the Covid-19 pandemic by 19,5%, while the remaining 80.5% was explained by other variables not included in this study. It can be concluded that the consumer behavior variable (X) during the Covid-19 pandemic had a significant effect on purchasing decisions (Y) for the basic needs of the community Banda Aceh City.Keywords: Covid-19 Pandemic, Consumer Behavior, Basic Needs